Fecal calprotectin levels in Helicobacter pylori gastritis in children - Aksoy, Özlem Yüksel; Canan, Oğuz; Hoşnut, Ferda Özbay; Akçay, EdaYılmaz; Özçay, Figen (The Turkish Journal of Pediatrics, 2020)
Background. Fecal calprotectin is an important inflammatory marker in intestinal diseases and is not routinely used in the upper gastrointestinal system disorders. The aim of this study was to show whether there is a relationship between fecal calprotectin levels and Helicobacter pylori (H pylori) gastritis in children and to determine the association of fecal calprotectin levels with gastric biopsy results in terms of chronic inflammation and neutrophil activity. Methods. Patients with the complaints of the upper gastrointestinal system (epigastric pain, heartburn, nausea and vomiting) who were planned to undergo endoscopy were enrolled prospectively. The presence of H pylori was defined according to the gastric antrum biopsy results. Fecal calprotectin level was tested in the stool sample of the patients. The fecal calprotectin levels, upper gastrointestinal endoscopy and gastric biopsy results of 89 patients were evaluated. Results. H pylori was found to be positive in the gastric biopsies of 51 (57.3%) patients. In the H pylori positive group mean fecal calprotectin level was 74.8 ± 67 μg/g, and in the H pylori negative group mean fecal calprotectin level was 52.7 ± 46 μg/g and the difference was significant (p= 0.039). We also found a significant relationship between fecal calprotectin levels and gastric neutrophil activity grades (p= 0.034). Conclusions. Mean fecal calprotectin levels were found to be higher in H pylori positive subjects in our study. Fecal calprotectin levels were correlated with gastric neutrophil activity grades. Fecal calprotectin represents gastric neutrophilic inflammation. When interpreting a high fecal calprotectin level, H pylori infection should be kept in mind.